Seals of the Khotyn County in the Interwar Period. Historical and Sphragistic Analysis - Калініченко, Віталій; Ільків, Микола; Rusnak, Oleksandr (Suceava, Codrul Cosminului, 2023)
In the article, the authors have made a detailed sphragistic and historical analysis of the matrix seals that were found on the territories of the former Khotyn County (Northern Bessarabia). Most of them are made of bronze and belong to the interwar period when the region was part of the Kingdom of Romania. The material under consideration has a significant factual and illustrative potential, especially in museum work. It testifies that the interwar activities of many organizations and institutions in the Khotyn County remain insufficiently studied or have not become the object of scientific research at all, which poses the issue in a new light.
Sigilii din județul Hotin în perioada interbelică: analiză istorică şi sfragistică
Keywords: Khotyn County; Hotin; Kingdom of Romania; interwar; sphragistics; matrix seals; organizations; institutions